Idea podejścia procesowego w zarządzaniu kancelarią doradztwa podatkowego - Szewc, Waldemar (The Idea of a Process Approach in a Tax Consulting Office Management, 2009)
The specificity of working in a tax consulting office creates conditions for using process management and it happens in a natural way. Law regulations and legal proceedings strongly determine rhythm of tax office activities. This kind of work is subordinated to market regulations and marketing rules. One can say that tax advising is a process of communications and knowledge transfer to clients. Basic elements of this process are: value for clients, knowledge, qualifications and experience, way of communication. These actions should be made more efficient in accordance with the idea of process management. In this range, the author shows a model of tax advising process where communication with the client has the most important meaning. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 97-105